Data lives : how data are made and shape our world - Kitchin, Rob (Bristol University Press, 2021)
Rob Kitchin explores how data-driven technologies have become essential to society, government and the economy. Blending scholarly analysis, biography and fiction, he demonstrates how data influence our daily lives.